2022
DOI: 10.1117/1.jatis.8.3.034003
|View full text |Cite
|
Sign up to set email alerts
|

Effective area calibration of the Nuclear Spectroscopic Telescope Array

Abstract: We present here the updated calibration of the Nuclear Spectroscopic Telescope Array, which was performed using data on the Crab accumulated over the last nine years in orbit. The basis for this new calibration contains over 250 ks of focused Crab observations (imaged through the optics) and over 500 ks of stray-light (SL) Crab observations (not imaged through optics). We measured an epoch averaged spectrum of the SL Crab data and define a canonical Crab spectrum of Γ ¼ 2.103 AE 0.001 and N ¼ 9.69 AE 0.02 keV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…We obtained that the FPMA fluxes in the 3-10 keV were slightly (≈ 5%) higher than for FPMB (with a 1-σ significance), while in the 10-25 keV range the fluxes between both cameras match up to 2% and this difference is less significant (< 1σ). This is within the calibration uncertainties of the instrument (Madsen et al 2015(Madsen et al , 2022. From these tests we concluded that both observations are compatible but with a small difference between the cameras.…”
Section: Nustarsupporting
confidence: 77%
“…We obtained that the FPMA fluxes in the 3-10 keV were slightly (≈ 5%) higher than for FPMB (with a 1-σ significance), while in the 10-25 keV range the fluxes between both cameras match up to 2% and this difference is less significant (< 1σ). This is within the calibration uncertainties of the instrument (Madsen et al 2015(Madsen et al , 2022. From these tests we concluded that both observations are compatible but with a small difference between the cameras.…”
Section: Nustarsupporting
confidence: 77%
“…To take into account NuSTAR calibration uncertainties (Madsen et al 2022), we assumed a gain offset free in the fit, obtaining −(0.085 ± 0.009) keV and −(0.068 ± 0.008) keV for the focal plane modules Aand B(FPMA and FPMB), respectively; similarly for IXPE calibration uncertainties (Di Marco et al 2022b), we left free the gain slope and offset obtaining a slope of 0.981 ± 0.003, 0.973 ± 0.003, 0.980 ± 0.003 keV −1 for the DU1, DU2, and DU3 respectively, while the offset in each one is 0.003 ± 0.012, 0.032 ± 0.012, and 0.020 ± 0.012 keV. As reported also by the photons fluxes of Table 2, the spectrum in the whole 2-8 keV IXPE energy band is dominated by the Comptonization component, while the disk contributes only at lower energies (see also Figure 8).…”
Section: Spectral Analysismentioning
confidence: 99%
“…Of the NuSTAR observations shown, this work is focused on the observation with the highest count rate, shown in red. (Madsen et al 2022), and does not occur when the data are processed with previous CALDB versions. The detector response is calculated across each FPM without taking into account pixel-to-pixel variations, which is responsible for the small differences (2%) seen in the MAXI J1803 spectra.…”
Section: Spectral Analysismentioning
confidence: 99%